Electrical-pulse-induced resistivity modulation in Pt/TiO2−δ/Pt multilayer device related to nanoionics-based neuromorphic function. (20th April 2017) - Kawamura, Kinya; Tsuchiya, Takashi; Takayanagi, Makoto; Terabe, Kazuya; Higuchi, Tohru
Abstract: Resistivity modulation behavior in Pt/TiO2−δ /Pt multilayer devices was investigated in terms of nanoionics-based neuromorphic function. The current relaxation behavior, which corresponds to short-term and long-term memorization in neuromorphic function, was analyzed using electrical pulses. In contrast to the huge difference in ionic conductivity for bulk crystal materials of TiO2−δ and WO3, the difference in the relaxation behavior was small. Rutherford backscattering spectrometry and hydrogen forward scattering spectrometry revealed that the TiO2−δ thin film contained 5.6 at. % of protons. This indicates that the neuromorphic function in TiO2−δ -based devices is caused by extrinsic proton transport, presumably through the grain boundary.